All in an afternoon: mixed breeding system in one-day lasting flowers of Hypericum elodes L. (Hypericaceae). (2nd September 2016) - Carta, A.; Savio, L.; Bedini, G.; Peruzzi, L.; Fisogni, A.; Galloni, M.
Abstract : Knowledge about mixed mating systems can improve our understanding of the evolutionary dynamics of reproductive systems. Here we report a study of the floral and reproductive biology of Hypericum elodes, an Atlantic-European soft-water pools specialist which shows a floral architecture consistent with both self- and cross-pollination. Controlled pollination experiments were performed in a natural population during three consecutive years. Marked flowers were monitored until fruit production, and laboratory germination experiments were conducted with the seeds produced. Plants were self-compatible (SCI>0.75), however, compared with selfing, cross-pollination enhanced fruit-set, seed-set and seedling growth, but not seed germination. Inbreeding depression (δ) was mild in the pre-dispersal stages (δ = 0.22 for fruit set, 0.18 for seed set and 0.13 for seed mass), low for germination percentage (δ = 0.003) and mild for seedling growth (δ = 0.23). The breeding system of H. elodes promotes outcrossing and assures reproductive success by means of competitive autogamy. Our results suggest a mixed mating strategy for the studied population, characterized by mild inbreeding depression (cumulative δ = 0.57), highlighting the benefit of this reproductive mode in unpredictable habitat, as the typical shallow-water meadows where H. elodes grows.